Pengembangan Handout tentang Identifikasi Ektoparasit pada Kelelawar pada Mata Kuliah Ekologi Hewan - Kencana, Bayu Tirta (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Learning handouts are printed teaching materials that contain important points of the material that will be presented or taught by students. This research aims to develop a handout on identifying ectoparasites in bats in animal ecology courses. The type of research used is development research using the 4D model approach (Define, Design, Develop, and Disseminate) which in Indonesian has been adapted into the 4P model (Definition, Design, Development, and Dissemination). However, in this development research, the researcher only reached the 3P stage (Definition, Design, and Development) which was validated by three expert validators (material or content expert, display expert, and language expert) and readability test by students. Based on the results of the validation analysis of teaching materials, it shows that the ecological handouts validated by three expert validators, namely material or content experts, are suitable for use without revision with an average score of 4.12, appearance experts are suitable for use without revision with an average score of 4. 28, and linguists are suitable for use without revision with an average score of 4, as well as a readability test by 15 students with an average score of 3 with a category suitable for use without revision. Therefore, the teaching materials in the form of ecological handouts developed are suitable for use by students.